ESTRUTURA POPULACIONAL DE DUAS ESPÉCIES DE CARANGUEJOS CHAMA-MARÉS (CRUSTACEA: DECAPODA: OCYPODIDAE) EM UM MANGUEZAL NO NORDESTE DO BRASIL - Pillon, Clarissa F.; Gonçalves, Alberto S.; Santos, Sandro; Castiglioni, Daniela da S. (Revista Nordestina de Zoologia, 2019)
We studied the population structure of the fiddler crabs Leptuca cumulanta and Leptuca leptodactyla, from Rio Formoso mangrove from southern coast of state of Pernambuco, Brazil, from April 2009 to March 2010. A total of 346 individuals of L. cumulanta were sampled: 211 males and 135 females. The species L. leptodactyla was 5.9 times more abundant than L. cumulanta, were sampled 2,029 individuals (1,405 males and 624 females). The size frequency distribution was normal and unimodal for both sexes in L. cumulanta, while in the species L. leptodactyla shows normal size-frequency distribution, being bimodal and unimodal in males and females, respectively. The mean size of the males and females of L. cumulanta did not differ, but males of L. leptodactyla reaching greater size than females. The overall sex ratio was skewed in favor of males in both species L. cumulanta - 1.56: 1; L. leptodactyla – 2:45: 1). In L. cumulanta males were predominantly right-handed, otherwise L. leptodactyla were left-handed. In general, population of L. cumulanta and L. leptodactyla are preserved in Rio Formoso mangrove and data was similar to those previously recorded for other species of the genus along the coast of Brazil, with exception of body size.